Contribuições ao estudo do transporte eletrônico em nanofios semicondutores : localização e estados de interface - Simon, Ricardo de Almeida (2013)
In this work, we studied the influence of surface charges on the properties (especially electronic transport) of semiconductor nanowires and nanobelts via computer simulations and also they were compared to experimental results. After a brief introduction over possible applications of nanowires and nanobelts and a discussion of the processes of growth and device building for characterization of the structures, the theoretical foundations required for the development of models and equations used to determine the electronic properties of some structures of interest were presented. The first developed model takes into account the effects of charges distributed randomly on the surface of structures and shows their contribution to confinement and electron distribution in the nanostructures. This idea was applied to In2O3 nanobelts based devices and showed that the presence of surface charges pushes electrons to the center of nanobelt, making the electron-electron scattering mechanism important in electron transport. This behavior was also observed experimentally through a resistance-temperature experiments where was observed a decreasing resistance for T < 77K. This behavior was observed in nanobelts presenting smaller width and disappearing with increasing dimensions of the nanobelt. Roughly speaking, calculation results agree with the experimental ones confirming that disorder leads to a superficial random potential which in turn, controls the electron flow in the nanobelt. In view of the above results, a model was developed to study the influence of the superficial disorder in the formation of metal-semiconductor interfaces required to build a real device. In this new model, we studied the effect of surface charges on the profile of the conduction band of a germanium nanowire device on which usual Schottky and Ohmic contacts were defined. Again the results show that the presence of the random potential leads to localization of surface charges, generating the so-called surface states, which in turn alters the profile of the conduction band in every direction of the nanowire. As a result some changes in the calculated electric current were observed. The main influence of surface states is the changing the transport mechanism: from thermionic emission to diffusion of carriers. Various current-voltage (I-V) curves were then simulated at different temperatures and investigating the evolution of the transport mechanisms with the variation of the surface state density, we observed a decrease of the value of Schottky barrier height. Experimental values of Schottky barrier height obtained from fitting I-V curves for germanium nanowire devices are satisfactorily close to the results that we have obtained for a surface states density of 1013cm􀀀2. With this model is possible to determine both the dominant mechanism of current transport and also the barrier height and density of surface states characteristics of the device.